Does Group-Based Incentive Pay Lead To Higher Productivity? Evidence from a Complex and Interdependent Industrial Production Process - Anders Frederiksen; Daniel Baltzer Schjødt Hansen; Colleen Flaherty Manchester (Institute of Labor Economics (IZA), 2022)
Group-based incentive pay is attractive in contexts where production is complex and interdependent, yet freeriding is a paramount concern. We assess the introduction of group-based performance pay in a modern industrial production setting using difference-in-difference estimation. Performance increased by 19 percent, with three quarters coming from increased performance of existing workers and the remaining from selection; workers became more efficient and were absent less often. We find little evidence of freeriding; quantile regressions show increased performance throughout the distribution of workers. Features of the design and implementation process created trust, a common goal, and a shared identity, which limited freeriding.
Keywords: M5; J33; L23; 330; difference-in-differences; performance pay; group-based incentive; freeriding; incentive effects; selection effects; absenteeism; efficiency; performance; productivity; trust